Odpowiedzi

  • Użytkownik Zadane
2009-12-14T11:33:21+01:00
A) x^9 - 64x^6 = x^6( x^3 - 64 )=x^6 (x^3 -4^3)=x^6(x-4)(x^2+8x+4)

b) 16x^4 - 1 = (16x-1)(16x³+16x²+16x++1)

c) (3x+1)^2 - x^2= 9x²+6x+1-x²=8x²+6x+1
1 2 1
Najlepsza Odpowiedź!
2009-12-14T11:48:44+01:00
Rozłóż na czynniki tzn. zapisz za pomocą mnożenia

a)
wzór do zastosowania: a³ - b³ = (a - b)(a² + 2a + b²)
x⁹ - 64x⁶ = x⁶( x³ - 64 ) = x⁶ (x³ -4³) = x⁶(x - 4)(x² + 8x + 4)

b) wzór do zastosowania: a² - b² = (a - b)(a + b)
16x⁴- 1 = (4x²)² - 1 = (4x² - 1)(4x² + 1)

c) wzór do zastosowania: a² - b² = (a + b)(a - b)
(3x+1)² - x²= [(3x + 1) + x][(3x + 1) - x] = (4x + 1)(2x + 1)
2009-12-14T12:37:59+01:00
A.
a³ - b³ = (a - b)(a² + 2a + b²)

x⁹ - 64x⁶ = x⁶( x³ - 64 ) = x⁶ (x³ -4³) = x⁶(x - 4)(x² + 8x + 4)

B.
a² - b² = (a - b)(a + b)
16x⁴- 1 = (4x²)² - 1 = (4x² - 1)(4x² + 1)

C.
a² - b² = (a + b)(a - b)
(3x+1)² - x²= [(3x + 1) + x][(3x + 1) - x] = (4x + 1)(2x + 1)

POZDRAWIAM :)